A preliminary study comparing the use of allogenic chondrogenic pre-differentiated and undifferentiated mesenchymal stem cells for the repair of full thickness articular cartilage defects in Rabbits - Dashtdar, H.; Rothan, H.A.; Tay, T.; Ahmad, R.E.; Ali, R.; Tay, L.X.; Chong, P.P.; Kamarul, Tunku (Wiley, 2011)
Chondrogenic differentiated mesenchymal stem cells (CMSCs) have been shown to produce superior chondrogenic expression markers in vitro. However, the use of these cells in vivo has not been fully explored. In this study, in vivo assessment of cartilage repair potential between allogenic-derived chondrogenic pre-differentiated mesenchymal stem cells and undifferentiated MSCs (MSCs) were compared. Bilateral full thickness cartilage defects were created on the medial femoral condyles of 12 rabbits (n = 12). Rabbits were divided into two groups. In one group, the defects in the right knees were repaired using alginate encapsulated MSCs while in the second group, CMSCs were used. The animals were sacrificed and the repaired and control knees were assessed at 3 and 6 months after implantation. Quantitative analysis was performed by measuring the Glycosaminoglycans (GAGs)/total protein content. The mean Brittberg score was higher in the transplanted knees as compared to the untreated knee at 6 months (p < 0.05). Quantitative analysis of GAGs was consistent with these results. Histological and immunohistochemical analysis demonstrated hyaline-like cartilage regeneration in the transplanted sites. Significant differences between the histological scores based on O'Driscoll histological grading were observed between contralateral knees at both 3 and 6 months (p < 0.05). No significant differences were observed between the Britberg, O'Driscoll scores, and GAGs/total protein content when comparing defect sites treated with MSC and CMSC (p > 0.05). This study demonstrates that the use of either MSC or CMSC produced superior healing when compared to cartilage defects that were untreated. However, both cells produced comparable treatment outcomes. (C) 2011 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 29: 1336-1342, 2011